The Influence of Product Quality and Service Quality on Customer Loyalty at PT. Industri Karet Deli - Nakata, Eko; Clara; Andi; Wilson, Vanness; kosasih, Denny; Leo Kendrew (Outline Publisher, 2024)
In the current era, along with the development of the times, transportation has become a tool that functions to transport goods and make it easier for people. In addition, transportation has a very important role in growing the pace of the economy in a country, therefore transportation is the most important element in the development of a country. In transportation there is an important part called a tire, one of the companies that produce tires is PT. Industri Karet Deli in this study analyzes the effect of product quality and service quality on customer loyalty, where PT. Industri Karet Deli is a company engaged in the purchase of raw rubber and processing this rubber into inner and outer tires for vehicles